2010
DOI: 10.1371/journal.pone.0013488
|View full text |Cite
|
Sign up to set email alerts
|

Silencing Mediated by the Schizosaccharomyces pombe HIRA Complex Is Dependent upon the Hpc2-Like Protein, Hip4

Abstract: BackgroundHIRA (or Hir) proteins are conserved histone chaperones that function in multi-subunit complexes to mediate replication-independent nucleosome assembly. We have previously demonstrated that the Schizosaccharomyces pombe HIRA proteins, Hip1 and Slm9, form a complex with a TPR repeat protein called Hip3. Here we have identified a new subunit of this complex.Methodology/Principal FindingsTo identify proteins that interact with the HIRA complex, rapid affinity purifications of Slm9 were performed. Multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 49 publications
1
39
0
Order By: Relevance
“…The pattern of yeast H3 DSI deposition thus resembles the one mediated by the HIRA complex for H3.3 incorporation in "higher" eukaryotes. Of note, in both S. cerevisiae and S. pombe, a homolog of the HIRA complex was identified with orthologs characterized for each component of this complex [82][83][84]. In S. cerevisiae, the Hir complex is one of the factors required for nucleosome reassembly after the passage of the RNA polymerase II, a mechanism that is proposed to play a critical role in transcription-coupled H3 deposition [85].…”
Section: Yeastmentioning
confidence: 99%
“…The pattern of yeast H3 DSI deposition thus resembles the one mediated by the HIRA complex for H3.3 incorporation in "higher" eukaryotes. Of note, in both S. cerevisiae and S. pombe, a homolog of the HIRA complex was identified with orthologs characterized for each component of this complex [82][83][84]. In S. cerevisiae, the Hir complex is one of the factors required for nucleosome reassembly after the passage of the RNA polymerase II, a mechanism that is proposed to play a critical role in transcription-coupled H3 deposition [85].…”
Section: Yeastmentioning
confidence: 99%
“…Mass spectrometric analysis of the fission yeast Slm9 has led to the identification of the 19S ATPase complex as the interacting proteins (27). The 19S ATPase complex is recruited to chromatin in a histone H2B ubiquitylation-dependent manner and plays a nonproteolytic role in Pol II transcriptional elongation in the budding yeast (58 -60).…”
Section: Discussionmentioning
confidence: 99%
“…2A). As Slm9 and Hip1 form a complex with two other proteins, Hip3 and Hip4 (26,27), we also examined these HIRA complex subunit disruptants. We found that both hip3⌬ and hip4⌬ cells showed the cross-tolerance-defective phenotype, similar to slm9⌬ and hip1⌬ cells (Fig.…”
Section: Fission Yeast Hira In Stress Responsementioning
confidence: 99%
See 2 more Smart Citations